Visualizing Digital Modulation Techniques with Simulink and Raspberry Pi 4 - Lydia Dede Obeng; Michael Aguadze; Isaac Papa Kwesi Arkorful (MSD Institute, 2025)
Digital modulation techniques are fundamental to modern communication systems, enabling the reliable transmission of data over wireless, optical, and wired channels. This research focuses on designing, implementing, and visualizing three key digital modulation schemes: Amplitude-Shift Keying (ASK), Frequency-Shift Keying (FSK), and Quadrature Phase-Shift Keying (QPSK) using MATLAB Simulink and the Raspberry Pi 4 platform. Performance evaluation through oscilloscope visualization demonstrated robust signal integrity: the 2-ASK transmitter exhibited clear amplitude changes at a 15 kHz carrier frequency, accurately representing binary data with minimal observed noise (qualitative SNR improvement over unmodulated signals) and negligible distortion. The 2-FSK transmitter produced distinct frequency shifts between 4.8 kHz and 9.6 kHz, encoding binary 1 and 0 with low error potential in noise-free conditions, as confirmed by waveform observations. The QPSK transmitter displayed smooth phase transitions at 15 kHz, cycling through four phase states (45°, 135°, 225°, 315°), effectively doubling the data rate compared to BPSK while maintaining phase accuracy within hardware latency limits (approximately 10-20 ms processing delay). The ability to visualize and analyze these methods supports the development of improved modulation schemes, contributing to more efficient and robust digital communication systems.